1983
DOI: 10.1126/science.6346488
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Major Neurofilament Subunit in Chicken Erythrocytes

Abstract: The 70,000-dalton core polypeptide of neurofilaments, thought to exist only in neurons, has been detected in chicken erythrocytes, where it coexists with vimentin and synemin as a component of the intermediate filament network. It is present in the circulating erythroid cells of embryos and young chickens but is nearly absent from the erythroid cells of adults. These findings are inconsistent with current models of intermediate filament expression, but provide another example of unexpected similarities between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Although SetD8 was not required for Ter119 induction in G1E-ER-GATA-1 cells grown under conventional conditions in a 2-d maturation assay, it repressed embryonic/ fetal β-like globin genes and additional genes expected to have important roles in cellular physiology. Our results establish the molecular underpinnings of a pivotal biological mechanism in which Vim (encoding Vimentin) is down-regulated during erythropoiesis as a key step in maturation-associated cytoskeletal remodeling (57). The loss of Vimentin-containing intermediate filaments has been proposed to be a prerequisite for enucleation (58).…”
Section: Discussionmentioning
confidence: 77%
“…Although SetD8 was not required for Ter119 induction in G1E-ER-GATA-1 cells grown under conventional conditions in a 2-d maturation assay, it repressed embryonic/ fetal β-like globin genes and additional genes expected to have important roles in cellular physiology. Our results establish the molecular underpinnings of a pivotal biological mechanism in which Vim (encoding Vimentin) is down-regulated during erythropoiesis as a key step in maturation-associated cytoskeletal remodeling (57). The loss of Vimentin-containing intermediate filaments has been proposed to be a prerequisite for enucleation (58).…”
Section: Discussionmentioning
confidence: 77%
“…NF proteins appear in central and peripheral neurons early during development, increasing in quantity, rapidly and progressively, throughout the cells of the nervous system during neurogenesis. While in situ hybridization studies have shown the neuronal specificity of NF gene expression, non-nerve cell expression does occur (Granger and Lazarides, 1983;Bennett and DiLullo, 1985;Gorza et al, 1988). NF proteins are expressed in bovine chromafFm cells in culture (Bader et al, 1984) and in a clonal line of pheochromocytoma (PC-12) cells (Lee et al, 1982;Franke et al, 1986).…”
Section: Indexing Terms: Cytoskeleton Intermediate Filaments Neuralmentioning
confidence: 99%
“…Although IF proteins of the neurofilament type are normally restricted to neurons, there are some reports on expression in non-neuronal cells as well (Granger and Lazarides, 1983). An interesting aspect of non-neuronal expression has been found in heart conduction myocytes where NF proteins are expressed together with desmin (Vitadello et al, 1990).…”
Section: Neuronal Intermediate Filaments Neurofilamentsmentioning
confidence: 99%